Variation in juvenile stages and success of male acquisition in Danish and French populations of the parasitic barnacle Sacculina carcini (Cirripedia: Rhizocephala) parasitizing the shore crab Carcinus maenas. Issue 2 (7th February 2019) - Rytter Jensen, Arn; Schneider, Mikkel Ree; Høeg, Jens T.; Glenner, Henrik; Lützen, Jørgen
ABSTRACT: Population and developmental characteristics of the rhizocephalan parasite Sacculina carcini were studied in the Limfjord, Denmark and at Roscoff, France. The frequency of juvenile externae in the Limfjord was higher during summer (69.8% of all externae) than during winter (43%). At Roscoff, 62.6% of externae were juvenile in May-June, but only 8.4% in September. The percentage of juveniles with settled males in the Limfjord was higher in summer (20.7% of all juveniles) compared to winter (6.7%). Juveniles at Roscoff in summer had less success in male acquisition (18.0%). The mean number of settled male cyprids per juvenile externa was 0.56 in summer and 0.12 during winter in the Limfjord, but only 0.27 in the summer at Roscoff. Laboratory kept virgin externae invaded by male cyprids ceased to attract additional males within 5–6 days after the first male settlement and then grew into adults within 3 weeks. Externae without males, kept in isolation, did not grow or show any other signs of maturation. Our results confirm and extend previous data on the role of males and their effect on externa development in S. carcini, and show that the success of male acquisition is susceptible to both seasonal and regional variation.